Speaking Skills in the Perspective of Malay Oral Literature: A Conceptual Study for the Strengthening of Indonesian Language Learning in Higher Education - Muliawiwin; Zaitun; Suhardi (Education Achievement: Journal of Science and Research, 2025)
Speaking proficiency is a language skill that has a strategic role in the academic and professional world. Despite this, many students still face various obstacles, especially in terms of vocabulary mastery, the use of proper intonation, and confidence when speaking. This research aims to offer a conceptual model of speaking learning based on Malay oral literature as a local cultural treasure rich in rhetorical value, diction choices, and aesthetic language styles. The method used in this study is a literature review by examining various theories about speaking fluency, classical and modern rhetorical concepts, and characteristics of Malay oral literature. The results of the study show that forms of oral literature such as pantun, poetry, gurindam, and traditional speech have relevant communicative values to be used as models in learning to speak. The concept offered in this article is in the form of a speaking learning model based on oral literature which consists of three stages, namely text exploration, rhetorical analysis, and speaking practice. This model is expected to strengthen students' speaking skills while fostering appreciation for the richness of local culture.